Assisted Suicide and Euthanasia: Language Lost in MAiD - Gromadzki, Rafal; Christie, Timothy (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
For most of Canada’s approximately 40-year debate on medically assisted death, euthanasia and assisted suicide were considered distinct issues. Yet in 2016 their ethical, psychological, and practical differences were effectively disregarded when the two acts were grouped together in the legislation under the umbrella term “Medical Assistance in Dying” (MAiD). The lack of distinction under the law of the two terms ignores important ethical considerations from the MAiD practitioners’ perspective. Although the principle of respect for autonomy must remain central to the assessments of MAiD eligibility, it cannot be the only consideration. This paper examines the ethical considerations and principles that underlie decisions to provide MAiD through an analysis of the progress, and results, of the 40-year debate on assisted suicide and euthanasia.